2010
DOI: 10.1179/1743288x10y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical models for pedometer use in physical activity interventions

Abstract: Background: Research shows that pedometers help to increase daily physical activity. However, much less is known about why pedometers work, specifically as it relates to the theoretical grounding of pedometerbased interventions.Objectives: To complete a full review of the literature regarding the use of theory and specific skills/tools used in pedometer-based interventions as it relates to changes in behaviour across time.Methods: Thirty-one original theoretically-based intervention studies were identified to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 57 publications
2
27
0
2
Order By: Relevance
“…The findings from research [23][24][25] are consistent with our study, as the patients were encouraged to increase their step target weekly and all sessions included aspects of counselling. Where our study contributes to literature in this area is that in many instances patients reported postprogramme increases in pedometer steps far in excess of the 1099 identified [25].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The findings from research [23][24][25] are consistent with our study, as the patients were encouraged to increase their step target weekly and all sessions included aspects of counselling. Where our study contributes to literature in this area is that in many instances patients reported postprogramme increases in pedometer steps far in excess of the 1099 identified [25].…”
Section: Discussionsupporting
confidence: 75%
“…Where our study contributes to literature in this area is that in many instances patients reported postprogramme increases in pedometer steps far in excess of the 1099 identified [25]. This finding is welcome given that the programme in our study was only 8 weeks in duration and included a more diverse group of cancer patients.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Kohl et al (2000) reviews various assessment techniques, citing articles dating back to 1971, and classifies techniques into six categories, including self-report (Sallis & Saelens 2000), direct observation (McKenzie 2002), indirect-, and direct calorimetry (Bailey et al 1995), doubly labeled water (Speakman 1998) and electronic or mechanical monitoring using e.g. pedometers (Saris & Binkhorst 1977, Lutes & Steinbaugh 2010 and accelerometry (Bouten et al 1997, Plasqui et al 2013. Activity monitoring tools in this last category have seen a surge in recent years due to their low cost and unobtrusive applicability.…”
Section: Physical Activity Monitoringmentioning
confidence: 99%